Respostas
respondido por:
1
Resposta:
Explicação passo-a-passo:
Determine essa equação abaixo
c) vejaaaaaa o (y) tem (+y) e (-y)
entao
pelo MÉTODO da ADIÇAO
{2x+y = 7
{4x - y= 11
2x + y = 7
4x - y = 11 SOMA
------------------------------------------
6x + 0 = 18
6x = 18
x = 18/6
x = 3 ( o Valor de (y)) UM dos DOIS
2x + y = 7
2(3) + y = 7
6 + y = 7
y = 7 - 6
y = 1
assim
x = 3
y = 1
emicosonia:
pronto
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás